THE EFFECT OF FIRM CHARACTERISTICS AND EARNING MANAGEMENT TOWARD SHARE RETURN: BEFORE AND DURING PANDEMIC - Calvina Hartanto; Candy Candy; Robin Robin (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The main purpose of investors investing in the firm stocks is to achieve wealth growth through stock return. Stock return is one of the most important factors in choosing the best investments. This study investigates the relationship between firm characteristics and earning management on stock return before and during the pandemic. It involves firms in the IDX Basic industry with the use of audited financial reports. In addition to tracing the results before and during the pandemic, this study also investigates the relationship between the before and during pandemic periods combined. The observation period is from 2016–2020, using balanced panel data to produce generalizable results. For data analysis, we use the multiple regression method to prove the hypothesis and will be tested using the application of Stata. The results obtained from this study show that before the pandemic, earning per share has a negative effect on stock return. During the pandemic, capital structure has a negative effect on stock return. While combining the period before the pandemic and during the pandemic, it is found that firm size and earning per share do affect the stock return. Firm size shows significant positive result, while earning per share shows significant negative on stock return. This finding suggests firms to maintain and improve these significant factors. Hence, it can increase investors’ confidence for investing in the firm.